Pengaruh Labelisasi Halal terhadap Keputusan Pembelian Konsumen dengan Minat sebagai Variabel Intervening pada Produk Stik Kelor : Studi Kasus pada Produk UMKM Stik Kelor di Daerah Kaloran Kota Serang - Alifia Devianty; Moh. Mukhsin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Labeling halal is a way to provide information that helps consumers identify the halal status of products on their packaging. With this halal labeling, the product can be regarded as halal, offering assurance and legal protection in line with Islamic law. The aim of this study was to assess the impact of halal labeling on consumer purchasing decisions, using interest as an intervening variable for Moringa Sticks products. The sampling method employed in this study was Nonprobability Sampling, involving a total of 100 respondents. Several tests were conducted, including data instrument tests, classical assumption tests, path analysis, hypothesis testing, and concluded with the Sobel test. The findings of this study indicate that the halal labeling variable (X) and purchase intention (Z) as an intervening factor do not have a significant impact on purchasing decisions (Y) for the Moringa Stik product.